PERSEPSI DAN SIKAP TENTANG KESEHATAN REPRODUKSI PADA REMAJA JALANAN DI PANTI ANAK JALANAN JL.GAJAH MADA KOTA MOJOKERTO - PRASETYAWATI, DENNY; DIANA, SULIS (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2015)
At this time, the social phenomenon of street children is very important in the life of a big city. Millions of children living and working on the streets, and many of those involved in survival sex where they exchange sex for food, money, security and illegal drugs. The threatening of HIV and AIDS cause sexual behaviors and the health of reproductive in the teenagers emerged. The purpose of this study is to describe the perceptions and attitudes about the health of reproductive in the streets teenagers the Orphanage of street children onGajah Mada street at Mojokerto. Design of this study is descriptive with public opinionsurvey, the variable is the perception and attitude about health of street all of teenagers reproductive in the streets teenagers. The population in this study is aged 10-24 years amount 41 people, techniques use accidental sampling in order to obtain 30 respondents. The study had been conducted on May 20, 2014 at Jl. Gajah Mada Mojokerto with using questionnaires. The data are collected through questionnaires will then be processed by editing, coding, scoring and tabulating. Analysis of the data uses T-scores. Based on the results of the study found that more than 50% have a positive perception amount 16 people (53.3%) and most have a negative attitude amount 22 people (73.3%). Perceptions and attitudes about the health of reproductive in the streets teenagers are affected by several factors consist of age, gender, education. Conclusions, the street teenagers in the study have positive perceptions but negative perception in their health of reproductive. Therefore, the health workers should provide counseling to the streets teenagers in order to solve problems of reproductive health.Keywords: Perception, Attitudes, The health of reproductive, Street teenagers